Peran Guru PAK dalam Pengembangan Materi Pembelajaran Nilai-Nilai Kristiani Pada Peserta Didik di SD Negeri 076067 Orahili, Nias Utara - Riahati Gea (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
This study aims to examine the role of Christian Religious Education (PAK) teachers in developing Christian values ​​learning materials for students at SD Negeri 076067 Orahili, North Nias. Christian values ​​are an integral part of character education taught in schools, which function to shape students' moral and ethical attitudes in everyday life. This study uses a qualitative literature approach to collect data on how PAK teachers develop learning materials that focus on Christian values. The results of the study indicate that PAK teachers have an important role in compiling learning materials that not only cover aspects of integrating Christian values ​​that are applied in learning activities and everyday life. The development of teaching materials has the opportunity from the resources and time available to explore Christian values ​​comprehensively. The conclusion in this paper shows that teachers in pedagogical competence can utilize human resources to develop more creative teaching materials based on Christian values, and are supported by adequate educational facilities.